First retrieval of tropospheric aerosol profiles using MAX-DOAS and comparison with lidar and sky radiometer measurements - H. Irie; Y. Kanaya; H. Akimoto; H. Iwabuchi; A. Shimizu; K. Aoki (Atmospheric Chemistry and Physics, 2008)
Ground-based Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) measurements were performed at Tsukuba, Japan (36.1° N, 140.1° E), in November–December 2006. By analyzing the measured spectra of scattered sunlight with DOAS and optimal estimation methods, we first retrieve the aerosol optical depth (τ) and the vertical profile of the aerosol extinction coefficient (k) at 476 nm in the lower troposphere. These retrieved quantities are characterized through comparisons with coincident lidar and sky radiometer measurements. The retrieved k values for layers of 0–1 and 1–2 km agree with lidar data to within 30% and 60%, respectively, for most cases, including partly cloudy conditions. Results similar to k at 0–1 km are obtained for the retrieved τ values, demonstrating that MAX-DOAS provides a new, unique aerosol dataset in the lower troposphere.